Oral Lichen Planus and Dental Implants: Protocol and Systematic Review - Torrejon-Moya, Aina (J Clin Med, 2020)
A systematic review was conducted to answer the following PICO question: “Can patients diagnosed with oral lichen planus (OLP) be rehabilitated with dental implants as successfully as patients without OLP?”. A systematic review of the literature was done following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statements to gather available and current evidence of oral lichen planus and its relationship with dental implants. The synthesis of results was performed using a Binary Random-Effects Model meta-analysis. Summary measures were odds ratios (ORs), frequencies, and percentages comparing the survival rate of dental implants placed in patients with OLP vs. those in patients without OLP. The electronic search yielded 25 articles, after removing the duplicated ones, 24 articles were selected. Out of the 24 articles, only 15 fulfilled the inclusion criteria. According to the results of the meta-analysis, with a total sample of 48 patients with OLP and 49 patients without OLP, an odds ratio of 2.48 (95% CI 0.34–18.1) was established, with an I(2) value of 0%. According to the Strength of Recommendation Taxonomy (SORT) criteria, level A can be established to conclude that patients with OLP can be rehabilitated with dental implants.